Phyto-ecological analysis of Phytolacca acinosa Roxb. assemblages in Kashmir Himalaya, India - Magray, Junaid A.; Wani, Bilal A.; Islam, Tajamul; Ganie, Aijaz H.; Nawchoo, Irshad A. (Frontiers in Forests and Global Change, 2022)
Phyto-ecological studies are essential in understanding community structure, organization and their response to changes in other environmental factors. In this study we analyzed the phytosociological and soil characteristics of Phytolacca acinosa communities and their correlation. 110 quadrats were laid across ten randomly selected sites in Kashmir Himalaya, India. Soil analysis was done using standard protocols. Overall, 161 species were recorded, belonging to 128 genera and 49 families. The species richness (SR) ranges from 27 to 83. Highest IVI was recorded for Poa angustifolia (60.06) and least for Berberis lycium, Abies pindrow, Plectranthus ragosus, and Ailanthus altissima (0.37 each). P. acinosa showed 100% random associations with other plant species. Soil properties varied significantly across the selected sites. Significant positive correlation was found between SR, OM (r=0.79), OC (r=0.79) and Shannon–Wiener index (H) (r=0.92). Nitrogen content also showed positive correlation with SR and H. Floristic composition of P. acinosa assemblages was governed by soil properties and habitat characteristics of sampling sites. Areas with highest floral diversity had high soil fertility while areas with low soil fertility possess lower diversity and need restoration. The knowledge may prove helpful in management of these habitats, boost conservation and mitigate the effects of changing climate.